Robinson Crusoe - Defoe , Daniel (Hong Kong Oxford university press, 2005)
"Robinson Crusoe" is a novel by Daniel Defoe, first published in 1719. It narrates the adventures of its protagonist, Robinson Crusoe, an Englishman who defies his family's wishes to pursue a life at sea. Crusoe's journey begins when he sets sail from England, despite his father's advice to lead a stable life. After surviving a shipwreck, he is captured by Moorish pirates and enslaved in North Africa. He eventually escapes, makes his way to Brazil, and becomes a successful plantation owner. Seeking to expand his wealth, he embarks on a voyage to West Africa to acquire slaves but is shipwrecked on a deserted island near the Orinoco River in Venezuela. Crusoe is the sole survivor of the wreck.
Keywords: English- Novel Book; Oxford English fiction book